2011
DOI: 10.1111/j.1442-200x.2010.03287.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine for transient hypothyroxinemia and cerebral palsy in extremely preterm infants

Abstract: Thyroxine supplementation for transient hypothyroxinemia of prematurity may reduce the incidence of CP in extremely preterm infants. Large-scale randomized controlled trials are essential to determine the effects of thyroxine supplementation in reducing the incidence of CP among extremely preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
9
0
2
Order By: Relevance
“…There were no short‐term beneficial effects of thyroxine treatment and sufficient neurodevelopmental data were lacking . One study of 60 ELGANs showed that levothyroxine treatment for free thyroxine levels of less than 0.8 ng/dL at the end of the first week of life could reduce the incidence of cerebral palsy, when compared to a former cohort of 54 ELGANs who did not receive treatment . However, we must be careful with these results, because a historical control group was used and cerebral palsy rates have generally decreased over time.…”
Section: Resultsmentioning
confidence: 99%
“…There were no short‐term beneficial effects of thyroxine treatment and sufficient neurodevelopmental data were lacking . One study of 60 ELGANs showed that levothyroxine treatment for free thyroxine levels of less than 0.8 ng/dL at the end of the first week of life could reduce the incidence of cerebral palsy, when compared to a former cohort of 54 ELGANs who did not receive treatment . However, we must be careful with these results, because a historical control group was used and cerebral palsy rates have generally decreased over time.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple clinical trials have been conducted, however a systematic review failed to find any significant difference in neonatal mortality, morbidity or neurodevelopmental outcomes in preterm infants who received thyroid hormones compared to controls (Osborn and Hunt, 2007). Since then, additional studies have been completed (Suzumura et al, 2011; Ng et al, 2014; Van Wassenaer-Leemhuis et al, 2014), however only Suzumura et al, found any neurodevelopmental benefit of thyroxine supplementation in preterm infants.…”
Section: Emergent Interventionsmentioning
confidence: 99%
“…Ancak düşük T4 düzeyleri ile gelişme geriliği ve serebral palsi arasında bir ilişki de gösterilmiştir [30]. Bir araştırmada 27 haftadan küçük olan prematürele-re LT4 verilmesi Bayley zihinsel gelişim skorunun kontrol grubuna göre daha yüksek bulunmasına yol açmıştır [31].…”
Section: İzlem Ve Tedavisiunclassified